Building long-term relationship with tertiary education graduates as a marketing challenge for a city - Wawrzyniec Rudolf (European Regional Science Association (ERSA), 2011)
The paper concerns the problem how local authorities should tackle with the problem of outward migration process. The dynamics of population development and migration in Europe and its regions have its influence on territorial cohesion and regional competitiveness. Migration is the process which from macroeconomic point of view has number of attitudes in Europe or in Member States. Unfortunately, when we look at that process from the single city or regional perspective it can have very negative effects into its socio-economic development. Usually the city/region which suffer from outward migration is losing the most valuable workforce - young, creative and tertiary educated graduates. The city/regional authorities should undertake measures aimed at keeping them at place. The best way to do that is stimulating the development of local economy in the long way, but this process, to be successful should be complemented by creative marketing action. The author is presenting the case study of the marketing programme implemented in 2008 in the post industrial city of Łodź, Poland (entitled: The Young Within the City of Łodź). The case study is an example of interesting approach to solve this very vital problem at the local labour market. The article present the complexity of the project, it shows how it correspond with the economic development strategy for the city. The partnership aspect is also undertaken in the context of successful delivering of the programme in the period 2008-2011). The city managers are collaborating with local universities, job agencies, and other partners. The author argue that successful marketing programme should not only concern image creation, but it should be designed for the benefit of the territorial client (in the case study: the current and prospect students in the city of Łodź). The author draw number of conclusions for other local authorities how to face similar difficulties in outward migration at the local labour market
Keywords: 330